Liver Preservation by Aortic Perfusion Alone Compared With Preservation by Aortic Perfusion and Additional Arterial Ex Situ Back-Table Perfusion With Histidine-Tryptophan-Ketoglutarate Solution: A Prospective, Randomized, Controlled, Multicenter Study. Issue 7 (July 2017) - Otto, Gerd; Heise, Michael; Thies, Jochen; Pitton, Michael; Schneider, Jens; Kaiser, Gernot; Neuhaus, Peter; Kollmar, Otto; Barthels, Michael; Geks, Josef; Bechstein, Wolf Otto; Hellinger, Achim; et al.
Abstract : Background: Arterial ex situ back-table perfusion (BP) reportedly reduces ischemic-type biliary lesion after liver transplantation. We aimed to verify these findings in a prospective investigation. Methods: Our prospective, randomized, controlled, multicenter study involved livers retrieved from patients in 2 German regions, and compared the outcomes of standard aortic perfusion to those of aortic perfusion combined with arterial ex situ BP. The primary endpoint was the incidence of ischemic-type biliary lesions over a follow-up of 2 years after liver transplantation, whereas secondary endpoints included 2-year graft survival, initial graft damage as reflected by transaminase levels, and functional biliary parameters at 6 months after transplantation. Results: A total of 75 livers preserved via standard aortic perfusion and 75 preserved via standard aortic perfusion plus arterial BP were treated using a standardized protocol. The incidence of clinically apparent biliary lesions after liver transplantation (n = 9 for both groups; P = 0.947), the 2-year graft survival rate (standard aortic perfusion, 74%; standard aortic perfusion plus arterial BP, 68%; P = 0.34), and incidence of initial graft injury did not differ between the 2 perfusion modes. Although 33 of the 77 patients with cholangiography workups exhibited injured bile ducts, only 10 had clinical symptoms. Conclusions: Contrary to previous findings, the present study indicated that additional ex situ BP did not prevent ischemic-type biliary lesions or ischemia-reperfusion injury after liver transplantation. Moreover, there was considerable discrepancy between cholangiography findings regarding bile duct changes and clinically apparent cholangiopathy after transplantation, which should be considered when assessing ischemic-type biliary lesions.